2013
DOI: 10.3390/f5010001
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Regeneration Patterns of Pinus nigra Subsp. salzmannii: Poor Evidence of Increasing Facilitation Across a Drought Gradient

Abstract: Tree recruitment is a key process underlying stand dynamics and sustainability in managed forests. Woody plant cover is known to affect the regeneration success of Pinus nigra, suggesting the existence of facilitative plant-plant interactions. The regeneration patterns of this Mediterranean pine were analyzed across its distribution area, using data from 3226 plots of the Spanish National Forest Inventory. We aimed to test the hypothesis that seedlings establishment occurs under higher values of either canopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 52 publications
2
17
1
Order By: Relevance
“…This disagreement with previous studies could be explained by the facts that (i) the area studied in the Navahondona forest was relatively small and did not include a latitudinal gradient, (ii) although the altitudinal gradient was strong (739 m), the most abundant shrub species were all Mediterranean and, consequently, shrub richness and diversity scores were not positively affected by the presence of a mixture of species with disparate biogeographical origins, (iii) and, compared with forests from northern Spain, shrub cover was much less in the study area (Table 1). Indeed, Pinus nigra forests from southern Spain attain the least shrub cover within the whole distribution area of this pine species (Tíscar & Linares, 2013). This circumstance could be related to forest structure according to results from the present study, but seed dispersal and herbivory could also be involved.…”
Section: Shrub Composition and Diversitysupporting
confidence: 61%
See 1 more Smart Citation
“…This disagreement with previous studies could be explained by the facts that (i) the area studied in the Navahondona forest was relatively small and did not include a latitudinal gradient, (ii) although the altitudinal gradient was strong (739 m), the most abundant shrub species were all Mediterranean and, consequently, shrub richness and diversity scores were not positively affected by the presence of a mixture of species with disparate biogeographical origins, (iii) and, compared with forests from northern Spain, shrub cover was much less in the study area (Table 1). Indeed, Pinus nigra forests from southern Spain attain the least shrub cover within the whole distribution area of this pine species (Tíscar & Linares, 2013). This circumstance could be related to forest structure according to results from the present study, but seed dispersal and herbivory could also be involved.…”
Section: Shrub Composition and Diversitysupporting
confidence: 61%
“…Sites with these topographical characteristics typically represent the coolest and rainiest habitats within mountainous areas; additionally, the lower temperatures and direct radiation results in lower potential evapotranspiration (Linares & Tíscar, 2011). Previous studies have found that summer drought is the main cause impeding Pinus nigra regeneration at the local (Tíscar & Linares, 2011) and regional scale (Tíscar & Linares 2013). Therefore, Pinus nigra seedlings may establish more successfully on shady aspect and higher altitude, where levels of soil-water availability are expected to be higher.…”
Section: Patterns Of Tree Regenerationmentioning
confidence: 99%
“…Several authors have cited a number of big problems for successful natural regeneration of Spanish black pine: irregular masting conditions, dry summers over a period of at least 3 years, excessive grazing and uncontrolled ploughing Lucas-Borja et al 2010Tíscar and Linares 2014). Moreover, forecasts suggest these pine forests will be soon one of the forest ecosystems hit hard by climate change, and their current distribution could shrink dramatically ).…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, the factors that affect pine recruitment in the Mediterranean Basin are more diverse and include changes in land use, forest succession, disturbance (fires), drought, gradients of light and nutrients, seed production, grazing pressure, or soil properties (for a review, see [29]). On a low scale, the studies that have focused on the recruitment dynamics of Mediterranean conifer species have found increasing seedling mortality in the summer [17][18][19][30][31][32]. Mediterranean ecosystems are characterized by long hot summers, with high irradiance and little, or no, precipitation, and these conditions strongly limit carbon assimilation [30,33].…”
Section: Introductionmentioning
confidence: 99%
“…On a low scale, the studies that have focused on the recruitment dynamics of Mediterranean conifer species have found increasing seedling mortality in the summer [17][18][19][30][31][32]. Mediterranean ecosystems are characterized by long hot summers, with high irradiance and little, or no, precipitation, and these conditions strongly limit carbon assimilation [30,33]. Post-fire Pinus halepensis regeneration can also be partially attributed to rainfall during the first wet seasons after fire [34], but light is expected to influence seed germination and seedling performance [4,17,35,36].…”
Section: Introductionmentioning
confidence: 99%